2014
DOI: 10.1556/achrom.26.2014.3.5
|View full text |Cite
|
Sign up to set email alerts
|

High-performance liquid chromatographic determination of montelukast sodium in human plasma: Application to bioequivalence study

Abstract: Summary.A simple, sensitive, and precise high-performance liquid chromatographic (HPLC) method for quantitation of montelukast in human plasma has been developed and validated. Commercially available candesartan cilexetil was used as an internal standard. After protein precipitation, montelukast and candesartan cilexetil (I.S.) in human plasma were analyzed using mobile phase containing 62% v/v acetonitrile and 38% v/v buffer (containing 1 mL L −1 triethylamine as peak modifier, final pH adjusted to 2.5 with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Literature survey reveals that several methods are reported for the estimation of Montelukast sodium using high-performance liquid chromatography [7,8], reverse phase high-performance liquid chromatography (RP-HPLC) with UV spectrophotometry [9,10], Capillary electrophoresis [11] and cyclic voltammetry [12]. However, there are limited methods for the determination of Montelukast Sodium-related impurities by RP-HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey reveals that several methods are reported for the estimation of Montelukast sodium using high-performance liquid chromatography [7,8], reverse phase high-performance liquid chromatography (RP-HPLC) with UV spectrophotometry [9,10], Capillary electrophoresis [11] and cyclic voltammetry [12]. However, there are limited methods for the determination of Montelukast Sodium-related impurities by RP-HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the analytical data of the present method for simultaneous colorimetric detection of four drugs using unmodied Au NPs as a probe. Compared with the performance of chromatographic [7][8][9][10][11][12][13][14] and spectrophotometric [16][17][18][19] methods for detection of four drugs, the present method demonstrated a lowered detection limit and a simplied procedure (without the any sample pretreatment at minimal volume of samples) (Table 2). Although LC-MS is an efficient tool for separation and determination of four drugs independently, the unmodied Au NPs-based colorimetric method is particularly attractive for simultaneous detection of four drugs because the color changes can be easily discerned with the naked-eye and then quantied by UV-visible spectrometry, which avoids tedious sample preparations and complicated instrumentation.…”
Section: Colorimetric Assay Of Four Drugsmentioning
confidence: 93%
“…[1][2][3][4][5][6] Identication and quantication of four drugs (venlafaxine; imipramine; amlodipine; alfuzosin) require a simple, specic and sensitive method for routine analysis of individual drug in biological samples. So far, various analytical techniques including high performance liquid chromatography (HPLC), [7][8][9][10] liquid chromatography with mass spectrometry (LC-MS), 14 capillary electrophoresis, 15 uorescence 16 and UV-visible spectrometry [17][18][19] have been used for the analysis of four drugs independently in pharmaceutical and biological samples. However, some of these methods are expensive, somewhat time consuming, they require derivatization steps and expensive instruments, which makes it unavailable in many laboratories for the analysis of four drugs in biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…It is a cysteinyl leukotriene receptor antagonist and used for treatment of asthma [ 9 ]. Some research studies were reported to determine MON as individual drug such as HPLC [ 10 , 11 ], spectrophotometric [ 12 , 13 ], and potentiometric [ 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%